1970
DOI: 10.1038/bjc.1970.54
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-producing Capacity in Human Cancer

Abstract: SUMMARY.-The antibody response to primary immunization with monomeric flagellin from Salmonella adelaide was studied in 61 patients with cancer and antibody-producing capacity was correlated with survival. In 27 patients suffering from " active " cancer, antibody-producing capacity was significantly depressed (P < 0 05) as compared with sick but not cancerous controls; in 13 such patients who survived more than 6 months after immunization, antibodyproducing capacity was moderately depressed, whereas in 14 who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1971
1971
1979
1979

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Our find ings also correlate nicely with the findings of Egan and Todd (1972) who demonstrated that more CEA could be obtained from the culture medium of colonic adenocarcinoma cells cultured in vitro than can be extracted from the cells. These findings may be associated with the reports that patients with metastatic nodules often have impaired cell-mediated immune reactions (Lenin et al, 1970;Lee et al, 1970;GaM et al, 1970) which have also been correlated with poor survival.…”
Section: Discussionsupporting
confidence: 59%
“…Our find ings also correlate nicely with the findings of Egan and Todd (1972) who demonstrated that more CEA could be obtained from the culture medium of colonic adenocarcinoma cells cultured in vitro than can be extracted from the cells. These findings may be associated with the reports that patients with metastatic nodules often have impaired cell-mediated immune reactions (Lenin et al, 1970;Lee et al, 1970;GaM et al, 1970) which have also been correlated with poor survival.…”
Section: Discussionsupporting
confidence: 59%
“…Antibody responses to antigen administration in cancer patients have been reported as being both normal (Leskowitz et al, 1957;Southam, 1968) and depressed (Lytton et al, 1964;Lee et al, 1970). Serum immunoglobulin levels in cancer patients have not been extensively investigated but Hughes (1971) found no significant differences in IgG, IgA, or IgM levels in 216 breast cancer patients as compared with 150 normal female controls.…”
Section: Discussionmentioning
confidence: 99%
“…2. Geometric mean peak titres in response to immunization with flagellin show ing data for healthy female controls, healthy male controls and hospital male controls [1], data obtained in present study for disease groups indicated, and data for patients with cancer [13]. Differences from controls were significant for bronchitis, infections and possibly for postgastrectomy states, and also for cancer [13], The hatched area represents IgG.…”
Section: Primary Response To Flagellinmentioning
confidence: 59%
“…However, it cannot be stated to what extent immunodepression is a cause or an effect of a particular chronic disease, be this cancer [13] or chronic infection. In the case of chronic infections including bronchitis, impaired antibody-producing capacity could result from effects such as antigenic overstimulation [14] and 'immune exhaustion', antigenic competition [15] or unrecognized effects of antibiotic treatment on immune function.…”
Section: Discussionmentioning
confidence: 99%